2014
DOI: 10.3390/s140304399
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoresis-Enhanced Detection of Deoxyribonucleic Acids on a Membrane-Based Lateral Flow Strip Using Avian Influenza H5 Genetic Sequence as the Model

Abstract: This study reports a simple strategy to detect a deoxyribonucleic acid (DNA) on a membrane-based lateral flow (MBLF) strip without tedious gel preparation, gel electrophoresis, and EtBr-staining processes. The method also enhances the detection signal of the genetic sample. A direct electric field was applied over two ends of the MBLF strips to induce an electrophoresis of DNAs through the strips. The signal enhancement was demonstrated by the detection of the H5 subtype of avian influenza virus (H5 AIV). This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Resonance light-scattering-based detections usually involve measuring the amount of light scattered by different light spectroscopy techniques, including localized surface plasmon resonance (LSPR) 52 , Raman spectroscopy 49 , 50 and dynamic light scattering (DLS) 51 , 53 . The colorimetric detection of viruses using AuNPs usually relies on two main techniques: 1) a color amplification technique in which AuNPs are applied to act as direct coloring labels with their characteristic, intense red color 55 , 58 , 59 , 66 ; and 2) color change technique in which a color change from red to purple occurs in response to particle aggregation. AuNP aggregation can be noncrosslinked aggregation caused by the target-triggered removal of stabilizing ligands from the surfaces of AuNPs 54 , 56 or interparticle-crosslinked aggregation caused by the binding of ligands on modified AuNPs with target analytes 57 , 67 .…”
Section: Key Functions Of Aunps In Virus Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resonance light-scattering-based detections usually involve measuring the amount of light scattered by different light spectroscopy techniques, including localized surface plasmon resonance (LSPR) 52 , Raman spectroscopy 49 , 50 and dynamic light scattering (DLS) 51 , 53 . The colorimetric detection of viruses using AuNPs usually relies on two main techniques: 1) a color amplification technique in which AuNPs are applied to act as direct coloring labels with their characteristic, intense red color 55 , 58 , 59 , 66 ; and 2) color change technique in which a color change from red to purple occurs in response to particle aggregation. AuNP aggregation can be noncrosslinked aggregation caused by the target-triggered removal of stabilizing ligands from the surfaces of AuNPs 54 , 56 or interparticle-crosslinked aggregation caused by the binding of ligands on modified AuNPs with target analytes 57 , 67 .…”
Section: Key Functions Of Aunps In Virus Detectionmentioning
confidence: 99%
“…The application of AuNPs in IAV detection has primarily been focused on developing assays that enable the direct detection of whole IAV particles 53 , 58 , 92 or viral RNA 64 , 66 , 67 , 70 , 71 , 83 , 86 through numerous AuNP-based fluorometric, SERS, scanometric, light-scattering, colorimetric, and electrochemical detection schemes (Table 1 ).…”
Section: Detection Of Specific Viruses Using Aunpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al applied a direct electric field to selectively enhance the transport of nucleic acids, and improve sensitivity 400-fold, in an LFA that detected PCR products from an H5N1 influenza PCR assay. 19 Although the application of ICP to micro/nanofluidic platforms was recently reviewed, 20 there are some examples of ICP in paper-based devices. Gong et al demonstrated ICP in a saturated paper-based device, which improved sensitivity 5-fold for a FITC-BSA conjugate and 4-fold for bromocresol green dye compared to without ICP; while Liu et al demonstrated ICP in a Parafilm-and paper-based device, which concentrated FITC.…”
Section: Electrophoreticmentioning
confidence: 99%
“…Our recent study revealed that an electric field could enhance the detection performance of single-trended Deoxyribonucleic acids (DNA) on the MBLF strips [20].…”
Section: Introductionmentioning
confidence: 99%